The role of alpha thalassaemia in unexplained microcytosis at the Wits academic hospital - Loonat, Sakina Bibi (My University, 2014)
At the University of Witwatersrand academic hospitals, unexplained microcytosis is a commonly encountered clinical problem. The differential diagnosis of microcytosis includes iron deficiency, anaemia of chronic disorder, sideroblastic anaemia (both congenital and acquired e.g. lead poisoning) and thalassaemia trait. α thalassaemia trait is most often not detected through conventional laboratory methods and molecular analysis becomes necessary in this setting.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Masters of Science, Johannesburg, 2013
Keywords: Thalassaemia